Integration and Islamisation Program for Clinical Post Graduate Students in International Islamic University of Malaysia (IIUM) - Yusof, Nazri Mohd (IIUM Medical Journal Malaysia, 2018)
Integration and islamisation (INI) programmes for undergraduate medical students have been practiced, reviewed and published in many journals. However, there is only a dearth of study on the implementation of such a programme for postgraduate clinical students. Hence, there is a need to examine such a programme because of the different learning environment and characteristic of the students. The aim of this paper is to examine the existing clinical postgraduate programme at IIUM and attempts to improve the INI curriculum. Method: The study employs an analytical method and important factors for the development of the curriculum are analysed to come out with the objective, content, teaching methodology and assessment method suitable for the program. Result: The study identified the important factors that determine the curriculum to be the needs of National Health Service, the mission of the university, the requirement of the professional body and characteristic of the students. The study proposes that the objective of the program is to produce holistic orthopaedic surgeons who understand the belief of Muslim patients and is able to facilitate them in their ibadah and daily life as a Muslims. This is achieved through offering a course which consists of 4 main subjects on the principles of shariah which include the element of Islamic worldview, fiqh ibadah, fiqh muamalah and Islamic moral values with emphasis on issues related to medicine. The teaching method proposed is having regular seminars which consist of presentations and discussion of important concept in Islamic fiqh and followed by case study on fiqh issues related to Medicine. Finally, the students should be assessed from the case write up which they are required to submit before they can sit for the final professional exam. Conclusion: This improved program enables students to complete their study without compromising their duties to provide services at their respective hospitals.